Pengaruh Media Sosial Terhadap Penggunaan Bahasa Indonesia Di Kalangan Generasi Muda - Arridha Silfani; Irfandi Bancin; Mahyul Syahputra Nasution; Sahmadi Harahap; Shella Sekar Wuni; Ana Theresia Br stepu; Nurmaya Sari; Mimi Rosadi (Menulis: Jurnal Penelitian Nusantara, 2025)
This study aims to examine the influence of social media on the use of Indonesian among the younger generation. Social media has become an inseparable part of everyday life, especially for teenagers and young adults. However, the use of language on platforms such as Instagram, TikTok, and Twitter often does not follow the rules of good and correct Indonesian. The method used in this study is descriptive qualitative with a literature study approach and observation of social media content used by students. The results of the study show that social media has a significant influence on the shift in language use, including the entry of foreign vocabulary, non-standard abbreviations, and a relaxed language style that tends to be informal. This has an impact on decreasing awareness of language in accordance with the Enhanced Spelling (EYD) and grammar rules. However, social media can also be used as a means of learning and promoting Indonesian if used wisely and creatively. Therefore, the role of education is very important in guiding the younger generation to use Indonesian appropriately in the digital era.